Fingertip Winding Suture: Pull-out Suture Technique for Flexor Tendon Repair in Zone I. Issue 4 (December 2017) - Mahmoud, Mostafa; Elian, Motaz; Seif Elnasr, Abdalah
Abstract : Injuries to flexor tendons in zone I has always been challenging during repair. Over the time several techniques were developed and modified to achieve the highest repair strength and thus the best functional outcome. These techniques vary from pull-out sutures with internal and external fixation to the use of bone anchors. All techniques were accompanied with advantages and disadvantages as well as postoperative morbidities related to certain techniques. In the present technique we introduce a subperiosteal pull-out suturing technique. It is a simple, strong, and cost-effective method for repair of flexor tendon injuries in zone I or in the context of tendon grafting.